Multimodal Critical Discourse Analysis of Educational TikTok Content: Knowledge Representation in the Short Video Era - Salsah Br Nainggolan; Yosi Evelyn Tondang; Putri Naira; Joice Stefanie Ginting; Dinda Rahmadani; Muhammad Natsir (International Journal of Education and Literature, 2026)
The swift proliferation of short-video-centric social media, notably TikTok, has revolutionized the educational landscape by facilitating novel methods of knowledge production, dissemination, and interpretation. This phenomenon denotes a transition in media and signifies an epistemological transformation in educational practices within the digital age. This study seeks to analyze the representation and interpretation of knowledge in TikTok educational content using a qualitative methodology grounded in an interpretive case study framework. Data were gathered via digital participant observation, comprehensive interviews, and document analysis involving 12 participants, comprising educational content creators and active TikTok users in higher education settings. Thematic data analysis was performed utilizing a Multimodal Critical Discourse Analysis framework to elucidate the interplay among visual, verbal, and auditory components in the construction of meaning. The results show three main patterns: the conflict between quick understanding and deep knowledge, the importance of emotional multimodal experiences in learning, and the negotiation of knowledge authority in changing digital spaces. These results indicate that learning via TikTok encompasses not only cognitive aspects but also intricate emotional, aesthetic, and social dimensions. This study theoretically enhances multimodal discourse analysis by integrating users' subjective experiences, while practically informing the advancement of critical digital literacy and the design of social media-based learning. Moreover, this study facilitates additional investigation into algorithmic dynamics, digital identity, and the evolution of learning methodologies within platform-centric contexts.